Desenvolvimento de uma abastecedora de fertilizantes de alta vazão - Howe, Marcio (2020)
Agribusiness in Brazil represents a fierce trade dispute between the major producers in the market, mainly in large scale agriculture. The search for efficiency and cost reduction demands high technology in the agribusiness sector, and also as the manufacturers of machines and implements in the chain. With culture windows increasingly shorter, for assertiveness in production, each minute is important. In the Cerrado, large equipment for the distribution of granulated fertilizers is used, for example the self-propelled products manufactured national or imported, that may have high technology, delivering agility and added value. Ergo, a minimum setup time is required to reach the maximum hours produced / day. Until 2017, the most used solution was the “Canudo”, characterized as an equipment to supply fertilizer in planters and distributors. However, this equipmen, demand an operating time incompatible with the current efficiency of the distributors. Meeting the proposed objective, the development of equipment with greater discharge capacity, minimized the setup time, which, figure up to the maneuvers and the supply of fertilizers at the distributor, comply with premises, with a series of safety requirements, standards, reliability, standardization and cost, as they are factors that impact the process, delivering significant gains of hectares / hour applied, fewer machines and operators in the process, allowing fertilizers that are applied at the right time, without harming the culture, as well as reducing the fixed assets of the farms, delivering the desired effectiveness and even financial savings to the customer.